Gallium complexes with α-diimine and phenazine in various reduced states. Issue 7 (4th December 2014) - Zhao, Yanxia; Liu, Yanyan; Wang, Zeyi; Xu, Wenhua; Liu, Bin; Su, Ji-Hu; Wu, Biao; Yang, Xiao-Juan
Abstract : Reaction of "digallane" with phenazine (Phz) leads to gallium complexes containing Phz and an α-diimine ligand in different reduced forms. Abstract : Reaction of α-diimine-stabilized "digallane" [Ga2 L2 ] with phenazine (Phz) leads to gallium complexes in which Phz and α-diimine show different reduced forms, demonstrating their noninnocence and diverse coordination modes.